Unlocking climate change resilience: Socioeconomic factors shaping smallholder farmers' perceptions and adaptation strategies in Mediterranean and Sub-Saharan Africa regions - Osama Ahmed; Mourad Faiz; Laamari Abdelali; Safwa Khoali; Cataldo Pulvent; Sameh Mohamed; Mame Samba Mbaye; Thomas Glauben (Regional Sustainability, 2025)
Climate change poses substantial challenges to agricultural productivity and sustainability, particularly in Mediterranean and Sub-Saharan Africa regions. Local smallholder farmers' adaptation strategies to climate change are crucial for mitigating these impacts. Therefore, this study investigated the socioeconomic factors influencing smallholder farmers' perceptions and adaptation strategies to climate change in four countries (Morocco, Egypt, Italy, and Senegal) of Mediterranean and Sub-Saharan Africa regions using a binary logistic regression (BLR) model. The results indicated that educational level, farming experience, agricultural income, farm size, participation in agricultural workshops, and training in Good Agricultural Practices (GAPs) significantly impacted smallholder farmers' perceptions and adaptation strategies to climate change (such as smallholder farmers adopting drought-tolerant crops). Higher educational level was linked to the greater possibility of smallholder farmers adopting drought-tolerant crops in Italy and Egypt, while gaps in rural education limited the possibility of smallholder farmers adopting drought-tolerant crops in Morocco and Senegal. Farming experience and agricultural income also enhanced the possibility of smallholder farmers adopting drought-tolerant crops, with notable variations across countries due to systemic barriers such as limited infrastructure in Senegal. Larger farm size and participation in agricultural workshops further improved the possibility of smallholder farmers adopting drought-tolerant crops, particularly in Morocco and Egypt. The findings highlighted the importance of tailored interventions and policy measures to support smallholder farmers in effectively responding to the challenges of climate change under diverse agricultural contexts. By understanding the specific needs and circumstances of smallholder farmers in these countries, policymakers can develop more effective adaptation strategies to enhance agricultural resilience and sustainability under the context of climate change.
Keywords: 330; climate change; Mediterranean and Sub-Saharan Africa regions; binary logistic regression (BLR) model; drought-tolerant crops; climate-smart agricultural practices